The Effect of Local Revenue and Balancing Funds on the Economy of Bali Province in 2012-2019 - Pradana, Asika Cahyaning Tiwi; Mun’im, Akhmad (Jurnal Bina Praja, 2022)
The implementation of Law Number 32 of 2004 concerning regional autonomy required Indonesia to change its economic development system from centralized to decentralized. One form was fiscal decentralization which aimed to promote social welfare and regional independence. However, the economic growth of several regions fluctuated, even though the fiscal decentralization instrument issued by the central government continued to increase. One of the provinces in Indonesia that have implemented a fiscal decentralization policy is Bali. It is categorized as one of the very-good provinces in terms of economic independence, reaching 53 percent, and tent to receive increasing local revenue every year. However, its economy seems to remain relatively high. This study aims to estimate the effect of fiscal decentralization as seen from PAD and balancing funds to the economic growth in districts/cities of Bali Province in 2012-2019. By using panel data regression analysis, this study examines the effect of PAD and balancing funds in the districts/cities of Bali Province and their effects on Bali’s economic growth. This study finds that the best model explaining the influence among those variables is the Fixed Effects Model (FEM) with Seemingly Unrelated Regression (SUR). The results show that the DAU and the combination of the utilization of regional income that includes PAD and other legal regional income have a positive and significant effect on economic growth in the districts/cities of Bali Province. Therefore, optimizing the use of regional revenues, both in the form of PAD and Other Legitimate Regional Revenues, may increase economic growth.